IMPROVING AGRICULTURAL INSURANCE BASED ON EXPERIMENTAL RESEARCH (Analysis of International Sciences, 2024)
In this article, experimental studies were carried out in order to clarify the practical situation of insurance of enterprises of the agriculture, recommendations are given for improving the industry.